Recent In-Situ Experiments for Energy-Related Materials from Soochow University-Western University Center for Synchrotron Radiation Research. Issue 2 (4th March 2017) - Zhong, Jun; Sun, Xuhui; Sham, Tsun-Kong
Abstract : Soochow University–Western University Center for Synchrotron Radiation Research (SWC or the Center) was officially founded in November 2012 based on an agreement between Soochow University, China, and Western University, Canada. The mandate of the Center is to promote synchrotron-based research through collaborations among Center members and other synchrotron scientists in both research and education, particularly in the fields of nanomaterials and devices, materials for energy and the environment, chemical biology, as well as the development and application of novel synchrotron capabilities and theory.